Opposing sequential biases in direction and time reproduction: Influences of task relevance and working memory. - Cheng, Si; Chen, Siyi; Shi, Zhuanghua (British Journal of Psychology, 2024)
Our current perception and decision‐making are shaped by recent experiences, a phenomenon known as serial dependence. While serial dependence is well‐documented in visual perception and has been recently explored in time perception, their functional similarities across non‐temporal and temporal domains remain elusive, particularly in relation to task relevance and working memory load. To address this, we designed a unified experimental paradigm using coherent motion stimuli to test both direction and time reproduction. The direction and time tasks were randomly mixed across trials. Additionally, we introduced pre‐cue versus post‐cue settings in separate experiments to manipulate working memory load during the encoding phase. We found attractive biases in time reproduction but repulsive biases in direction estimation. Notably, the temporal attraction was more pronounced when the preceding task was also time‐related. In contrast, the direction repulsion remained unaffected by the nature of the preceding task. Additionally, both attractive and repulsive biases were enhanced by the post‐cue compared to the pre‐cue. Our findings suggest that opposing sequential effects in non‐temporal and temporal domains may originate from different processing stages linked to sensory adaptation and post‐perceptual processes involving working memory.